Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1094/phyto-05-19-0166-rvw
|View full text |Cite
|
Sign up to set email alerts
|

Mycoviruses in Biological Control: From Basic Research to Field Implementation

Abstract: Mycoviruses from plant pathogens can induce hypovirulence (reduced virulence) in their host fungi and have gained considerable attention as potential biocontrol tools. An increasing number of mycoviruses that induce fungal hypovirulence, from a wide variety of taxonomic groups, are currently being reported. Successful application of these viruses in disease management is greatly dependent on their ability to spread in the natural populations of the pathogen. Mycoviruses generally lack extracellular routes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 91 publications
0
70
0
Order By: Relevance
“…Since we only observe sectorisation and hypovirulence in the isolates of two groups (Groups 1 and 2), vegetative incompatibility with Group 3 could possibly explain the high virulence and stability of the Group 3 isolates [31,32]. The difference in toxin production between the in vitro conditions and the rice sheath could also indicate that the isolates of Groups 1 and 2 are indeed infected with a mycovirus [39]. Brusini and Robin (2013) [40] observed that the transmission rate of mycoviruses is higher in the host plant of the pathogenic fungus, leading to more symptoms of the viral infection in planta than in vitro.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since we only observe sectorisation and hypovirulence in the isolates of two groups (Groups 1 and 2), vegetative incompatibility with Group 3 could possibly explain the high virulence and stability of the Group 3 isolates [31,32]. The difference in toxin production between the in vitro conditions and the rice sheath could also indicate that the isolates of Groups 1 and 2 are indeed infected with a mycovirus [39]. Brusini and Robin (2013) [40] observed that the transmission rate of mycoviruses is higher in the host plant of the pathogenic fungus, leading to more symptoms of the viral infection in planta than in vitro.…”
Section: Discussionmentioning
confidence: 96%
“…The spread of these mycoviruses occurs mainly through hyphal anastomosis. This process of horizontal gene transmission occurs between vegetative compatible isolates [24,36,39]. Since we only observe sectorisation and hypovirulence in the isolates of two groups (Groups 1 and 2), vegetative incompatibility with Group 3 could possibly explain the high virulence and stability of the Group 3 isolates [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Even when the virus is successfully cured from a virus-infected fungal cell, impairments caused by the treatment make the cured fungal cell inappropriate for investigations of fungal-mycoviral interactions. In the method for securing an artificial virus-infected strain, infectious cDNA clones of a fungal virus for artificial infection were transformed into the virus-cured fungal strain upon integration of the infectious clones into the fungal genome based on Koch's postulates 15 . However, this method is also challenging because of the difficulty in the case of multi-segmented mycovirus 15 and the alteration of gene expression with non-homologous chromosomal integration, such as ectopic recombination 16 .…”
mentioning
confidence: 99%
“…In the method for securing an artificial virus-infected strain, infectious cDNA clones of a fungal virus for artificial infection were transformed into the virus-cured fungal strain upon integration of the infectious clones into the fungal genome based on Koch's postulates 15 . However, this method is also challenging because of the difficulty in the case of multi-segmented mycovirus 15 and the alteration of gene expression with non-homologous chromosomal integration, such as ectopic recombination 16 . Therefore, in our previous investigation of PoV in P. ostreatus, virus-curing was performed by the mycelial fragmentation method followed by single colony isolation 17 .…”
mentioning
confidence: 99%
See 1 more Smart Citation